Left dislocation in national varieties of English: functions and frequency - Goylo, Artem A. (Journal of the Belarusian State University. Philology, 2021)
The article describes the results of a corpus study of left dislocation in Jamaican, Indian, and Canadian English. Jamaican and Indian varieties of English serve as examples of outer-circle varieties whereas Canadian English is an example of inner-circle varieties (in terms of the three circles model of World Englishes by B. Kachru). Attention is paid to the structural peculiarities of left dislocation: special agreement patterns and the usage of prepositions with dislocated constituents. Usage of special agreement forms between resumptive pronouns and dislocated constituents in Jamaican English is explained by Jamaican Creole influence. The frequency of left dislocation with respect to different types of discourse is established – we conclude that left dislocation is more frequent in informal settings, and that the distribution of this construction is influenced by the individual style of a speaker. The classification of the functions of left dislocation is expanded to include functions that are specific to the varieties of the outer circle. Most uses of left dislocation in outer-circle varieties can be analysed in terms of the classification by E. Prince and E. Manetta, put forward to explain left dislocation in inner-circle varieties, which leads to the conclusion that there are only minor differences in functions of this non-canonical construction between the studied varieties.
Keywords: sociolinguistics; corpus linguistics; syntactic variation; national varieties of English; left dislocation